2010
DOI: 10.1243/14644193jmbd266
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of road friction on driveline vibrations

Abstract: The aim of this article is to assess the influence of the tyre/road contact interface on driveline vibrations. The mode shapes of a vehicle driveline are obtained and analysed, initially using three tyre models: a simple torsional spring, linear slip, and relaxation length-based models. Additionally, a fully transient load-and slip-dependent non-linear relaxation length model is incorporated into the driveline to determine the dynamic response on different surfaces. Simulations of pull-away manoeuvres on vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The tire is modeled in this study based on the same principle of a published work in this area by Sharp and Jones [21], Pacejka [22], and Bartram et al [8], which includes the tire torsional stiffness and the vertical stiffness, expressed as and , respectively, as shown in Figure 4. The hub, the rim, and the brake disc are lumped together as one rotating inertia due to the rigid connection.…”
Section: Powertrain Torsional Vibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The tire is modeled in this study based on the same principle of a published work in this area by Sharp and Jones [21], Pacejka [22], and Bartram et al [8], which includes the tire torsional stiffness and the vertical stiffness, expressed as and , respectively, as shown in Figure 4. The hub, the rim, and the brake disc are lumped together as one rotating inertia due to the rigid connection.…”
Section: Powertrain Torsional Vibrationmentioning
confidence: 99%
“…It is found that the frequency of longitudinal vibration mainly depends on the engine output torque increase rate, gear position, and engine flywheel mass moment of inertia through experiments [7]. In addition, the literature [8] has studied the effect of road surface on the half-shaft torque fluctuation, indicating that the vibration frequency and amplitude of the half-shaft torque are closely related to the conditions of the road surface. From this point of view, road conditions may influence the vehicle longitudinal vibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bartram et al. 13 used different tire models to analyse the influence of road surface adhesion coefficient on the low frequency longitudinal vibration of the drivetrain. In Wellmann and Govindswamy, 14 a multi-body system approach was adopted to analyse launch shudder in rear wheel-driven vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In Wellmann et al, 12 the effects of various subsystem parameters on the performance of the transmission system NVH were studied through simulation and experiment on the basis of the established dynamic model of the transmission system. Bartram et al 13 used different tire models to analyse the influence of road surface adhesion coefficient on the low frequency longitudinal vibration of the drivetrain. In Wellmann and Govindswamy, 14 a multi-body system approach was adopted to analyse launch shudder in rear wheel-driven vehicles.…”
Section: Introductionmentioning
confidence: 99%